High hydrostatic pressure assisted extraction of pectin from sugar beet pulp. (20th May 2021) - Kaya, Burcu; Okur, Ilhami; Alpas, Hami; Oztop, Mecit Halil
Summary: This study aimed to investigate the effect of high hydrostatic pressure assisted extraction (HHPE) (250, 350 and 450 MPa at 40 °C for 5 min with/without acid addition) of pectin from sugar beet pulp and compare its properties with pectin obtained from conventional extraction (CE). Degree of esterification (DE), galacturonic acid (Gal‐A) content, Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR) relaxometry experiments were performed on the obtained pectin powder. HHPE (12.23 ± 0.13%) doubled extraction yield compared to CE (6.43 ± 0.07%). Also, HHPE and acid addition were found to have a synergetic effect on the extraction. HHPE resulted in degradations in the polymer structure and reduced Gal‐A content and DE. Pectin extracted with both methods was classified as low methoxyl pectin (LMP). According to the NMR Relaxometry results, HHPE decreased water holding capacity (WHC). In brief, HHP was shown to increase the pectin extraction yield and no changes in viscosity were observed at the concentrations studied (2 g/L). Abstract : Sugar beet is an important agricultural crop for countries producing sucrose. The pulp remaining after the beet juice extraction contains significant amount of fiber and this fiber is quite rich in pectin. Pectin is an important food hydrocolloid that has many uses in food industry as a stabilizer; thickener and gelling agent. In this, study extraction yield of pectin from sugar beet was increased through High‐Hydrostatic Pressure application and the obtained pectin was further characterized by NMR Relaxometry; rheology and FTIR experiments.